Pengembangan Perangkat Pembelajaran Berdiferensiasi untuk Meningkatkan Keterampilan Numerasi Peserta Didik UPT SMA Negeri 9 Bone - Dinipatriany, Andi; Daud, Firdaus; Arsyad, Muhammad (Jurnal Ilmiah Kanderang Tingang, 2024)
Development of Differentiated Learning Tools to Improve Students' Numeracy Skills on Climate Change and Global Warming Material (supervised by Firdaus Daud and Muhammad Arsyad). This development research aims to produce differentiated learning tools that are valid, practical and effective for improving Numeracy skills on climate change and global warming material. The development model used in this research refers to the ADDIE development model developed by Robert Marie Branch (2009) which includes 5 stages, namely (1) Analysis, (2) Design, (3) Development, (4) Implementation, (5) Evaluation. The tools developed in this research are Learning Implementation Plans (RPP), Student Worksheets (LKPD), modules, HOTS assessment instruments, and multiple representation ability instruments. The quality testing stage of the differentiated learning tools and supporting instruments that will be used in the research is carried out through a validity test given to two validators. Field trials were carried out on class X 1 students totaling 30 people. The results of the research show that the differentiated-based learning tools developed meet product quality, namely: 1) validity including: (a) lesson plans with a value of 3.48 (valid), (b) LKPD with a value of 3.58 (very valid), ( c) module with a score of 3.40 (valid), and (d) Numeracy skills assessment instrument with a score of 0.77 (valid); 2) practicality includes: (a) implementation of learning tools with a score of 1.80 in the fully implemented category, (b) teacher response to learning tools with a score of 93.42% in the very practical category; 3) effectiveness includes assessment of Numeracy skills with a pretest average of 14.30% in the low category and a posttest average of 78.01% in the medium category and N-gain results of 0.76 in the high category. Thus, the research results show that learning tools based on the Differentiated learning model have valid, practical and effective qualities.